THE INFLUENCE OF THINK PAIR SHARE COOPERATIVE LEARNING STRATEGIES AND INTERPERSONAL COMMUNICATION AGAINST THE LEARNING RESULTS OF THE QUR'AN HADITH STUDENTS OF MADRASAH TSANAWIYAH NEGERI 2 DELI SERDANG - Fatimah Zamzam MG (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study was to determine: (1) the effect of TPScooperative learning strategies on learning outcomes of Al-Qur'an HadithMTs Negeri 2 Deli Serdang students, (2) the influence of interpersonalcommunication on learning outcomes of Al-Qur'an Hadith students ofMTs Negeri 2 students Deli Serdang, and (3) the interaction of TPScooperative learning strategies and interpersonal communication to thelearning outcomes of Al-Qur'an Hadith of MTs Negeri 2 Deli Serdangstudents. The study was conducted at MTsN 2 Deli Serdang. This type ofresearch is a quasi-experimental. The study population was all grade VIIstudents spread over 3 classes. The sampling technique used is clusterrandom sampling. Data collection instruments are questionnaires andtests. The data analysis technique used is the analysis of two-path variancein testing α = 0.05. The results showed: (1) the average learning outcomesof Al-Qur'an Hadith students who were taught with the TPS learningstrategy were higher than the average learning outcomes of the Al-Qur'anHadith students who were taught with strategies expository learning. (2)the average learning outcomes of Al-Qur'an Hadith students with highinterpersonal communication is higher than the learning outcomes of Al Qur'anHadith students with low interpersonal communication, and (3)there is an interaction between learning strategies and interpersonalcommunication.